Lessons from a comparative study of user involvement. Issue 8 (16th November 2016) - Gutman, Carolyn; Ramon, Shulamit
Abstract: Grounded in the context of the significant differences in service user involvement in social work education and research between the UK and Israel, a joint project between Anglia Ruskin University in the UK and Tel-Hai College in Israel was developed. Its aim was to develop a comparative research methodology to evaluate the outcomes of service user involvement in social work education. A main tenet of our research methodology consisted of partnering with a group of older people who used health and social care services as co-researchers from each country. This co-researching methodology together with the evaluation tools worked effectively in the two respective countries. The key findings highlight that while students in both countries valued the involvement of service users in their training, this occurred more so in Israel, where this is a very new development. Students in both countries developed rich concept maps illustrating the complexity of such an involvement. Yet, while the responses of both groups to vignettes describing user involvement scenarios reflected the positive impact of such an involvement, the UK students focused on the negative impact of potential risk more so than the Israeli students.